1990
DOI: 10.1128/mcb.10.3.1017
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in RAD6, a yeast gene encoding a ubiquitin-conjugating enzyme, stimulate retrotransposition.

Abstract: The Saccharomyces cerevisiae DNA repair gene RAD6 encodes a ubiquitin-conjugating enzyme which polyubiquitinates histones in vitro. Here we show that mutations in rad6 increase the frequency of transposition of the retrotransposon Ty into the CANI and URA3 loci. Using isogenic RAD6 and rad6 strains, we measured a more than 100-fold increase in the spontaneous rate of retrotransposition due to rad6, although there was no increase in the Ty message level. This is the first time that a mutation in a host gene has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 39 publications
4
37
1
Order By: Relevance
“…We previously reported that a deletion of RAD6 dramatically increases the rate of transposition of Ty1 into the CAN1 gene (54). This is in contrast to our finding, presented here, that deletions of RAD6 cause only a marginal increase in the transposition of Ty1 into the promoterless his3 target.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We previously reported that a deletion of RAD6 dramatically increases the rate of transposition of Ty1 into the CAN1 gene (54). This is in contrast to our finding, presented here, that deletions of RAD6 cause only a marginal increase in the transposition of Ty1 into the promoterless his3 target.…”
Section: Discussioncontrasting
confidence: 57%
“…Mutations in RAD6 increase the overall rate of Ty1 transposition into CAN1 and SUP4 without causing an increase in the level of total Ty1 RNA (8,31,54). However, when genetically marked Ty1 elements were used, it was determined that the deletion of RAD6 affected the transposition of some, but not other, elements, and these effects were at the transcriptional level (8).…”
mentioning
confidence: 99%
“…The conspicuous and pleiotropic phenotype of ubc2(rad6) null mutations (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) stands in contrast to the relatively mild phenotype of ubrl null mutations, which also inactivate the N-end rule pathway (11). Thus, unlike N-recognin, whose known functions are confined to the N-end rule pathway (11), the UBC2 enzyme is an essential component not only of this pathway but at least of one other Ub-dependent pathway as well.…”
Section: Methodsmentioning
confidence: 99%
“…Two of the yeast UBC enzymes have been identified as the products of the previously known genes RAD6 (renamed UBC2) (22), which participates in DNA repair, induced mutagenesis, sporulation (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), and suppression of retrotransposition (34), and CDC34 (renamed UBC3), which is required for the transition from G1 to S phase of the cell cycle (35). Two of the other yeast UBC enzymes, UBC4 and UBC5, have been shown to be required for most of the Ub-dependent protein degradation in this organism (18,36).…”
mentioning
confidence: 99%
“…Though rhp6 and its homologs in other species have been known for several years, its actual biochemical function has not been clear. Earlier reports have demonstrated elevation and randomization of Ty transposition in the vicinity of certain genes in rad6 Ϫ mutants in S. cerevisiae (37,47), suggesting that Rad6 may affect the chromatin structure of the genes so as to make them better targets for Ty transposi- a Quantitation by densitometry of the autoradiograph shown in Fig. 8B.…”
Section: Fig 6 Increased Methylase Accessibility Of the Mat2p Locusmentioning
confidence: 99%